2014
DOI: 10.1521/aeap.2014.26.5.411
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Local Change Team Intervention on Staff Attitudes Towards HIV Service Delivery in Correctional Settings: A Randomized Trial

Abstract: The National Criminal Justice Drug Abuse Treatment Studies research program conducted cluster randomized trials to test an organizational process improvement strategy for implementing evidence-based improvements in HIV services for preventing, detecting, and/or treating HIV for individuals under correctional supervision. Nine research centers conducted cluster randomized trials in which one correctional facility used a modified Network for Improvement of Addiction Treatment (NIATx) change team approach to impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…The CJ-DATS: HIV-STIC intervention is the only study found as part of this review that examined an implementation strategy targeting organizational-level barriers to improve uptake of HIV services across the care continuum. 28,35,41,60 Emerging findings from this study suggest a complex interaction of staff and system level factors that influence the successful rollout and uptake of evidence-based practices for HIV for inmates. Future research that employs a multi-level, ecological model to examine implementation facilitators and barriers at system-, staff-, and inmate-levels will help inform the development of implementation strategies for linkage programs that can successfully work within correctional settings and that will allow the scale-up and sustainability of efficacious programs across various correctional and community settings.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The CJ-DATS: HIV-STIC intervention is the only study found as part of this review that examined an implementation strategy targeting organizational-level barriers to improve uptake of HIV services across the care continuum. 28,35,41,60 Emerging findings from this study suggest a complex interaction of staff and system level factors that influence the successful rollout and uptake of evidence-based practices for HIV for inmates. Future research that employs a multi-level, ecological model to examine implementation facilitators and barriers at system-, staff-, and inmate-levels will help inform the development of implementation strategies for linkage programs that can successfully work within correctional settings and that will allow the scale-up and sustainability of efficacious programs across various correctional and community settings.…”
Section: Discussionmentioning
confidence: 83%
“…36,59,60 Correctional agencies’ focus on security contrasted with the HIV community agencies’ focus on health and well-being of inmates. Additionally, policies and procedures within corrections agencies also hindered implementation of programs.…”
Section: Implementation Of Hiv Testing and Linkage To Hiv Community Cmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Local change teams doubled the odds of successful delivery of HIV services (point estimate for odds ratio ¼ 2.14) and increased health care staff perceptions of the value of HIV services compared to the control group. 19,20 From a public health viewpoint, the disproportionate burden of HIV in incarcerated populations presents both a challenge and an opportunity. Correctional facilities provide an opportunity to engage a traditionally ''hard to reach'' demographic that often slips through the conventional community-based health system.…”
Section: Discussionmentioning
confidence: 99%